Clinical and laboratory features associated with myeloperoxidase expression in pediatric B‐lymphoblastic leukemia. Issue 4 (13th October 2020) - McGinnis, Eric; Yang, David; Au, Nicholas; Morrison, Douglas; Chipperfield, Kate M.; Setiadi, Audi F.; Liu, Lorraine; Tsang, Angela; Vercauteren, Suzanne M.
Abstract: Background: B‐lymphoblastic leukemia (B‐ALL) is the most common childhood malignancy, and its diagnosis requires immunophenotypically demonstrating blast B cell lineage differentiation. Expression of myeloperoxidase (MPO) in B‐ALL is well‐described and it has been recognized that a diagnosis of mixed phenotype acute leukemia should be made cautiously if MPO expression is the sole myeloid feature in these cases. We sought to determine whether MPO expression in pediatric B‐ALL was associated with differences in laboratory, immunophenotypic, or clinical features. Methods: We reviewed clinical, diagnostic bone marrow flow cytometry, and laboratory data for all new B‐ALL diagnoses at our pediatric institution in 5 years. Cases were categorized as MPO positive (MPO+) or negative (MPO−) using a threshold of ≥20% blasts expressing MPO at intensity greater than the upper limit of normal lymphocytes on diagnostic bone marrow flow cytometry. Results: A total of 148 cases were reviewed, 32 of which (22%) were MPO+. MPO+ B‐ALL was more frequently hyperdiploid and less frequently harbored ETV6‐RUNX1 ; no MPO+ cases had KMT2A rearrangements or BCR‐ABL1 . Although not significantly so, MPO+ B‐ALL was less likely than MPO− B‐ALL to have positive end‐of‐induction minimal residual disease studies (9.4 and 24%, respectively), but relapse rates and stem cell transplantation rates were similar between groups. Aberrant expression of other more typically myeloid markers was similar between these groups. Conclusion: In our study cohort, MPO+ B‐ALL showed minimal residual disease persistence less often after induction chemotherapy but otherwise had similar clinical outcomes to MPO− B‐ALL, with similar rates of additional myeloid antigen aberrancy.